The Meaning of Health in Rural South Africa: Gender, the Life Course, and the Socioepidemiological Context - Mojola, Sanyu A.; Ice, Erin; Schatz, Enid; Angotti, Nicole; Houle, Brian; Gómez-Olivé, F. Xavier (Population and development review, 2022)
This article examines the meaning of health among middle-aged and older adults in a rural South African setting, where 72 percent of adults aged 40 and over are living with a major chronic condition, and 81 percent report good or very good health. We draw on a unique mixed-methods dataset that includes a population-based survey with disease biomarkers (hypertension, diabetes, HIV), self-assessments of health including self-rated health, functional ability and medication use, as well as nested qualitative life history interviews with survey participants including questions about lived experiences of health. We conduct survey trend analysis and ordinal logistic regression, as well as inductive and deductive coding of qualitative interviews, and triangulate findings across data sources. Overall, we find that self-rated health and functional ability are not associated with biometric disease indicators; however, we find that gendered familial expectations, life course stage, and the socioepidemiological context work together to regulate the salience of illness as people age. The study highlights the utility of research with multiple measures of health in illuminating the challenges of aging amidst the complex epidemiological transitions that increasingly characterize low- and middle-income countries.